Adhesion and Interface Studies of the Structure‐Controlled Polyimide with Smooth Copper for High‐Frequency Communication. Issue 5 (5th January 2022) - Zhong, Ao; Li, Jinhui; Zhang, Guoping; Sun, Rong
Abstract: Fan‐out wafer‐level packaging (FOWLP) is expected to become the dominating trend in millimeter wave and 5G communication. However, the reliability faces enormous challenges due to the inherent poor adhesion between the insulating layer of polyimide (PI) and copper wirings in FOWLP. Herein, adhesive polyimide (API) with improved adhesion on smooth Cu by the introduction of benzimidazole and siloxane structure is reported. The results prove that the adhesion strength is increased by 191.46% compared with the conventional PI, owing to the generation of Cu complexes by benzimidazole as well as the cooperation of the flexible siloxane segments. Besides, the APIs not only hold a proper coefficient of thermal expansion (CTE) of 6.28 × 10 −6 K −1 matching with Si wafers (2.5 × 10 −6 K −1 ), but also possess CTE (18.56 × 10 −6 K −1 ) of API‐3 matching with Cu circuits (17 × 10 −6 K −1 ), so that a low residual stress of −1.849 MPa is obtained. Moreover, superior mechanical, thermal properties are also obtained, of which the modulus and tensile strength are 6.31 GPa and 170 MPa, while T g and T 5% are as high as 474.6 and 524.57 °C, respectively. Therefore, the as‐prepared high‐performance APIs can be prospective candidates in FOWLP for high‐frequency communication. Abstract : Adhesive and high‐performance polyimides with high adhesion strength on smooth Cu (191.46% increased), low coefficient of thermal expansion, low residual stress, as well as superior mechanical and thermal properties have been proposed and successfully synthesized by the introduction of benzimidazole and siloxane structure, which can be prospective candidates in fan‐out wafer‐level packaging for high‐frequency communication.